Inter-rater reliability of neck reflex points in women with chronic neck pain - Weinschenk, Stefan; Hollmann, Markus W.; Hotz, Lorenz; Picardi, Susanne; Strowitzki, Thomas (Forschende Komplementärmedizin, 2016)
Neck reflex points (NRP) are tender soft tissue areas of the cervical region that display reflectory changes in response to chronic inflammations of correlated regions in the visceral cranium. Six bilateral areas, NRP C0, C1, C2, C3, C4 and C7, are detectable by palpating the lateral neck. We investigated the inter-rater reliability of NRP to assess their potential clinical relevance. Methods: 32 consecutive patients with chronic neck pain were examined for NRP tenderness by an experienced physician and an inexperienced medical student in a blinded design. A detailed description of the palpation technique is included in this section. Absence of pain was defined as pain index (PI) = 0, slight tenderness = 1, and marked pain = 2. Findings were evaluated either by pair-wise Cohen's kappa or by percentage of agreement (PA). Results:Examiners identified 40% and 41% of positive NRP, respectively (PI > 0, physician: 155, student: 157) with a slight preference for the left side (1.2:1). The number of patients identified with >6 positive NRP by the examiners was similar (13 vs. 12 patients). values ranged from 0.52 to 0.95. The overall kappa was = 0.80 for the left and = 0.74 for the right side. PA varied from 78.1% to 96.9% with strongest agreement at NRP C0, NRP C2, and NRP C7. Inter-rater agreement was independent of patients' age, gender, body mass index and examiner's experience. Conclusion: The high reproducibility suggests the clinical relevance of NRP in women.
Gesehen am 09.06.2020